2018
DOI: 10.1007/s42010-018-0029-5
|View full text |Cite
|
Sign up to set email alerts
|

Interrelations between motivational regulation, procrastination and college dropout intentions

Abstract: Procrastination can theoretically be conceived of as a motivational selfregulatory failure and is assumed to be a risk factor of college dropout in the higher education context. It was hypothesized that students' procrastination and college dropout intentions are closely related with their motivational regulation-in terms of the effectiveness of their efforts to self-regulate their motivation and in terms of the strategic knowledge behind the actual regulation attempts (conditional knowledge about the suitabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 54 publications
5
36
1
5
Order By: Relevance
“…In line with our third hypothesis, we found significant correlations of the different phases with emotional, motivational, behavioural as well as cognitive/affective variables associated with student dropout. The direction of the correlations is consistent with previous findings (e.g., Bäulke et al, 2018;Heublein et al, 2017;Krejtz & Nezlek, 2016;Ruthig et al, 2007), since subjective well-being, academic self-concept and subjective task value correlated negatively with the phases of intentions to quit studies completely and intentions to change a major, whereas there were positive correlations of the assumed phases with anxiety, academic procrastination and learned helplessness. This finding is in line with the assumed process model.…”
Section: P R E P R I N Tsupporting
confidence: 91%
See 1 more Smart Citation
“…In line with our third hypothesis, we found significant correlations of the different phases with emotional, motivational, behavioural as well as cognitive/affective variables associated with student dropout. The direction of the correlations is consistent with previous findings (e.g., Bäulke et al, 2018;Heublein et al, 2017;Krejtz & Nezlek, 2016;Ruthig et al, 2007), since subjective well-being, academic self-concept and subjective task value correlated negatively with the phases of intentions to quit studies completely and intentions to change a major, whereas there were positive correlations of the assumed phases with anxiety, academic procrastination and learned helplessness. This finding is in line with the assumed process model.…”
Section: P R E P R I N Tsupporting
confidence: 91%
“…Taking a behavioural variable into account, academic procrastination (a voluntary delay of an intended action despite knowing about its negative consequences; Grunschel et al, 2016;Klingsieck, 2013;Simpson & Pychyl, 2009;Steel, 2007) was found to be positively linked to dropout intentions (Bäulke et al, 2018).…”
Section: Correlates Associated With Student Dropoutmentioning
confidence: 99%
“…When confronted with disappointment or increasing cost, motivation regulation (Miele and Scholer 2018) could be an element that mediates change in student dropout intention. Research on motivational regulation revealed its beneficial effect on student performance and well-being, as well as its mediating role in predicting study dropout (Bäulke et al 2018;Grunschel et al 2016). A more thorough understanding of the motivation regulation process could aid the work of student counselors.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, dropout intention is considered as an early warning sign for study dropout (Brandstätter et al 2006), and is widely used in recent studies which investigate dropout phenomena (cf. Bäulke et al 2018;Suhlmann et al 2018). Practically, investigating the formation of dropout intention at an early stage enables practitioners to design tailor-made counseling services right at the beginning of the decisionmaking process.…”
Section: Research On Study Dropout and Study Dropout Intentionmentioning
confidence: 99%
“…We thus recommend that future research test the proposed predictors in samples of non-completers. However, it should be noted that the relationship between dropout intention and actual dropout has long been emphasized in the literature (e.g., Bean and Metzner 1985;Bäulke et al 2018;Cabrera et al 1993;Mashburn 2000), indicating that studying dropout intentions is still a valuable approach (see also, e.g., Litalien and Guay 2015). In addition, we focused on master's students, and relying on a sample from this population might have influenced our findings.…”
Section: Limitations and Future Lines Of Researchmentioning
confidence: 97%